Impact of Covid-19 on Zimbabwean Immigrants and Refugees - NOMLALA, Bomi Cyril; CHIHNAMO, Edmore (International Journal of Environmental, Sustainability, and Social Science, 2023)
COVID-19's outbreak in China at the end of 2019 and its expansion to South Africa have had a detrimental socioeconomic impact on Zimbabwean migrants and refugees in South Africa and immigrants and refugees are the hardest hit during the pandemic. The South African government's lockdown measures resulted in the shutdown of non-essential industries such as travel and tourism, construction, and e-hailing services, where most Zimbabwean migrants and refugees work as frontline workers. Some individuals are employed by shady businesses that can't afford to pay them during downtime. Others ran unregistered enterprises that were denied access to business relief packages due to technicalities. Furthermore, only a small percentage of the estimated 2 million Zimbabwean immigrants and refugees are documented to meet the access requirements for the aid packages. The government's ostensibly all-encompassing COVID-19 relief package requirements were as disparate as they were on paper. Negative nationalism, which sparked xenophobic attacks in 2008, 2015, and 2019, appears to underpin the government's foreign policy framework and attitude. According to the findings, the lockdown resulted in the loss of work, abject poverty, and broken marriages among Zimbabwean immigrants. To live, many turned to prostitution, drug dealing, and rampant opportunism.